2015
DOI: 10.31028/ji.v10.i2.125-136
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kelayakan Finansial Pengembangan Sistem Irigasi Cakram Otomatis Bertenaga Surya di Nusa Tenggara Barat

Abstract: This study evaluates the result of implementation of water-efficient irrigation technology by using an automated roundshaped emitter, powered by solar cell. In order to determine investment feasibility of the automated system, Net Present Value (NPV), Internal Rate of Interest (IRR) and Benefit Cost Ratio (BCR) analysis have been conducted. An investment is feasible if the project fulfill the following criteria: (1) NPV is greater than zero, (2) IRR is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This will minimize water waste by distributing the water equally and straight to the root zone of the plant. When plants receive the right amount of water based on their demands, their growth and productivity are enhanced [29]. The goal of drip irrigation, which applies water in small amounts and continuously, is to keep soil moisture levels high enough to meet plant water requirements.…”
Section: ) Drip Irrigation System Scenariomentioning
confidence: 99%
“…This will minimize water waste by distributing the water equally and straight to the root zone of the plant. When plants receive the right amount of water based on their demands, their growth and productivity are enhanced [29]. The goal of drip irrigation, which applies water in small amounts and continuously, is to keep soil moisture levels high enough to meet plant water requirements.…”
Section: ) Drip Irrigation System Scenariomentioning
confidence: 99%
“…A business feasibility study is a decision-making tool needed to assess and decide whether a business activity/project is feasible or not to be carried out [16]. An investment is said to be feasible if it meets the following criteria: (1) NPV is greater than zero, (2) IRR is greater than the current discount rate, (3) BCR is greater than 1 [17]. In addition to NPV, BEP and IRR, there are various methods for evaluating investment feasibility, namely the Annual Equivalent (AE) Method and the Payback Period (PBP) Method) [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agus et al (2003) reported that the use of irrigation pumps in horticultural crops such as water melons in Central Lampung provided economic benefits. Further, implementation of automatic disc irrigation systems by solar powered on mango trees in Pringgabaya, West Nusa Tenggara at laboratory and field scales was economically feasible, with an average return of capital in fourth year (Rejekiningrum and Saptomo 2015).…”
Section: Water Use Efficiencymentioning
confidence: 99%